EVALUASI TINGKAT PENERAPAN BIOSEKURITI PADA PETERNAKAN AYAM BROILER DI KECAMATAN MAIWA KABUPATEN ENREKANG: EVALUATION OF THE LEVEL OF IMPLEMENTATION OF BIOSECURITY IN BROILER CHICKEN FARMING IN MAIWA DISTRICT ENREKANG REGENCY - Rahmi, Helmi Rafia; Nugraha, Angga; Purnomo, Nurul (Universitas Boyolali, 2025)
This study aimed to evaluate the level of biosecurity implementation in broiler chicken farms in Maiwa District, Enrekang Regency. Biosecurity is an important component on the livestock health management system that aims to prevent the entry and spread of diseases, and maintain productivity of livestock businesses. The study was conducted descriptively and quantitatively with a survey approach to the entire population of broiler chicken farmers in the area, which amounted to 27 people. Data collection was conducted through direct observation, through direct observation, interviews, and questionnaires. The aspects studied include three main components of biosecurity: traffic control, sanitation, and isolation. The results of this study showed that the implementation of biosecurity by farmers was generally in the sufficient category. The sanitation aspect was the most dominantly implemented, marked by waste management, which had been carried out very well by all respondents (100%). The isolation aspect also showed quite good implementation, with most farmers having separated sick and dead chickens and isolation cages. However, the implementation of biosecurity in the aspect of traffic control is still not optimal, Particularly in relation to guest entry procedures and vehicle disinfectant spraying. Farmers’ characteristics such as education level, farming experience, and gender are known to influence variations in biosecurity implementation. This study is expected to provide a real picture of the field and be a consideration for farmers, the government, and related parties in improving the implementation of biosecurity as a whole.